127k views
4 votes
What is the factorization of the trinomial below -x^2+x+42

User Emesday
by
4.5k points

2 Answers

1 vote

Answer:-1(x-7)(x+6)

Explanation:

Apex

User NickDK
by
5.2k points
6 votes
For the given trinomial


a=-1, b=1 ,c=42

We need to multiply a by c

-1 * 42 = - 42

We split the middle term with these two factors

image
To obtain,


- {x}^(2) + 7x -6x + 42
We now factor


- {x}^(2) + x + 42 \: = x( - x + 7) + 6( - x + 7)
This implies


- {x}^(2) + x + 42: = (x + 6)(7 - x)
User Elle Imhoff
by
5.3k points